Performance Analysis Of A Probalistic Re-Entrant Line In An Environment Stress Testing Operation - -, Suresh Kumar (2007)
The Environmental Stress Testing (EST) is a reliability test function in a semiconductor back-end manufacturing industry. This thesis focuses on the development of an analytical model based on the extension of the mean value analysis (MVA) equations for a queueing network model.